A Case of Solid-type Adenoid Cystic Carcinoma in the Upper Trachea Found by Diplopia - Higashi, Yasuyuki; Nemoto, Kazuki; Kawanami, Toshinori; Yamasaki, Kei; Morimoto, Toshiki; Noguchi, Shingo; Tachiwada, Takashi; Yatera, Kazuhiro; Nakamura, Midori; Uchimura, Keigo (The Journal of the Japan Society for Respiratory Endoscopy, 2019)
Background. Adenoid cystic carcinoma (ACC) of the trachea is rare. ACCs are categorized into cribriform, tubular and solid types, and solid type is known to have the poorest prognosis. Case. A 57-year-old Japanese man who had suffered from diplopia for 2 months visited a hospital. Head magnetic resonance imaging (MRI) showed a right intraorbital tumor and multiple brain tumors, and chest computed tomography (CT) revealed multiple bilateral pulmonary nodules. He was introduced to our hospital for further examinations, and chest CT at the first visit showed a thickened tracheal wall in the right upper ventral trachea and multiple bilateral pulmonary nodules. Positron emission tomography (PET)-CT demonstrated a mild fluorodeoxyglucose (FDG) uptake (maximum standardized uptake value 5.4) in the tracheal lesion. Bronchoscopic findings revealed a submucosal tumor with vascular hyperplasia in the right upper ventral trachea with magenta coloring on autofluorescence imaging. Histopathologically, the biopsied specimen obtained from the lesion was diagnosed as solid-type ACC arising in the trachea. Conclusion. Our patient with solid-type ACC of the trachea had accompanying diplopia but showed no respiratory symptoms. ACC of the trachea sometimes show asymptomatic intramural progression without any respiratory symptoms, so physicians should be alert for this disease.